Finite Element Modal Analysis of the Duplex Face Gear - Ge Shengli; Huang Guanming (Jixie chuandong)
Taking a new type of gear drive-the duplex face gear as study object,the solid model of the duplex face gear is established by using the Creo software. The former 6 order of natural frequencies and principal vibration shapes are calculated through the modal analysis by using the finite element analysis software Workbench,the influence of material on natural frequency and principal vibration shapes are discussed. The results indicate that the modal vibration shapes are first order radial direction,second order radial direction,torsional vibration. The results are verified by experiment,the theory basis for the dynamic response analysis and structure design of the duplex face gear transmission system is provided.